Coronary plaque and clinical characteristics of South Asian (Indian) patients with acute coronary syndromes: An optical coherence tomography study. (15th November 2021) - Nakajima, Akihiro; Subban, Vijaykumar; Russo, Michele; Bryniarski, Krzysztof L.; Kurihara, Osamu; Araki, Makoto; Minami, Yoshiyasu; Soeda, Tsunenari; Yonetsu, Taishi; Crea, Filippo; Takano, Masamichi; Higuma, Takumi; et al.
Abstract: Background: South Asians, and Indians in particular, are known to have a higher incidence of premature atherosclerosis and acute coronary syndromes (ACS) with worse clinical outcomes, compared to populations with different ethnic backgrounds. However, the underlying pathobiology accounting for these differences has not been fully elucidated. Methods: ACS patients who had culprit lesion optical coherence tomography (OCT) imaging were enrolled. Culprit plaque characteristics were evaluated using OCT. Results: Among 1315 patients, 100 were South Asian, 1009 were East Asian, and 206 were White. South Asian patients were younger (South Asians vs. East Asians vs. Whites: 51.6 ± 13.4 vs. 65.4 ± 11.9 vs. 62.7 ± 11.7; p  < 0.001) and more frequently presented with ST-segment elevation myocardial infarction (STEMI) (77.0% vs. 56.4% vs. 35.4%; p  < 0.001). On OCT analysis after propensity group matching, plaque erosion was more frequent (57.0% vs. 38.0% vs. 50.0%; p  = 0.003), the lipid index was significantly greater (2281.6 [1570.8–3160.6] vs. 1624.3 [940.9–2352.4] vs. 1303.8 [1090.0–1757.7]; p  < 0.001), and the prevalence of layered plaque was significantly higher in the South Asian group than in the other two groups (52.0% vs. 30.0% vs. 34.0%; p  = 0.003). Conclusions: Compared to East Asians and Whites, South Asians with ACS were younger and more frequently presented with STEMI. Plaque erosion was the predominant pathology for ACS in South Asians and their culprit lesions had more features of plaque vulnerability. Clinical Trial Registration: http://www.clinicaltrials.gov, NCT03479723 Graphic abstract: Unlabelled Image Highlights: South Asians with ACS were younger and more frequently presented with STEMI. Plaque erosion was the predominant pathology for ACS in South Asians. South Asian patients had more features of plaque vulnerability in culprit lesions.